Role of genetic and electrolyte abnormalities in prolonged QTc interval and sudden cardiac death in end-stage renal disease patients. - Monica Coll; Carles Ferrer-Costa; Sara Pich; Catarina Allegue; Emilio Rodrigo; Gema Fernández-Fresnedo; Paloma Barreda; Jesus Mates; Angel Luis Martinez de Francisco; Israel Ortega; Anna Iglesias; Oscar Campuzano; et al. (PLoS ONE)
Background Patients with end-stage renal disease have very high mortality. In individuals on hemodialysis, cardiovascular deaths account for ~50% of all deaths in this population, mostly due to arrhythmia. To determine the causes of these arrhythmic deaths is essential in order to adopt preventive strategies. The main objective of this study was to investigate whether, the presence of QTc interval alterations, from electrolyte abnormalities or presence of rare genetic variants, could have a relationship with sudden arrhythmogenic deaths in end-stage renal disease patients. Methods We recorded the pre- and post-dialysis QTc interval in 111 patients undergoing hemodialysis. In 47 of them, we analyzed 24 SCD-related genes including the most prevalent genes associated with long QT syndrome using a custom resequencing panel. Results We found a positive although not significant association between the presence of long QTc and mortality in a subset of end-stage renal disease patients. In addition, in five patients with long QTc only after dialysis (21.7%) we detected rare potentially pathogenic genetic variants. Three out of these five carriers subsequently died suddenly. Conclusions Genetic background may be determinant in the risk of sudden cardiac death in these patients. We recommend evaluating the QTc interval before and after hemodialysis, and performing a genetic analysis of individuals with long QTc after hemodialysis.